Single-Nucleus Transcriptomic Analysis Reveals Important Cell Cross-Talk in Diabetic Kidney Disease - Wei, Yi; Gao, Xiang; Li, Aihua; Liang, Mengjun; Jiang, Zongpei (Frontiers in Medicine, 2021)
Diabetic kidney disease (DKD) leads to the loss of renal function and cell cross-talk is one of the crucial mechanisms participating in the pathogenesis of DKD. However, the mechanisms of cell communication were not fully elucidated in previous studies. In this study, we performed cell cross-talk analysis using CellPhoneDB based on a single-nucleus transcriptomic dataset (GSE131882) and revealed the associations between cell communication-related genes and renal function, providing overall insight into cell communication in DKD. In addition, this study may facilitate the discovery of novel mechanisms, promising biomarkers, and therapeutic targets that are clinically beneficial to patients.